2022
DOI: 10.1093/g3journal/jkab433
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly of the fully mycoheterotrophic orchid Gastrodia elata

Abstract: Gastrodia elata, an obligate mycoheterotrophic orchid, requires complete carbon and mineral nutrient supplementation from mycorrhizal fungi during its entire life cycle. Although full mycoheterotrophy occurs most often in the Orchidaceae family, no chromosome-level reference genome from this group has been assembled to date. Here, we report a high-quality chromosome-level genome assembly of G. elata, using Illumina and PacBio sequencing methods with Hi-C technique. The assembled genome size was found to be 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The genome of G. elata has been continuously reported in recent years, offering insights into how G. elata adapted to heterotrophy in Mycena and Armillaria . In G. elata , genes important in the control of flowering time, the circadian clock, nutrient absorption, immunity, growth of the roots and leaves, and photosynthesis were all severely lost ( Yuan et al., 2018 ; Park et al., 2020 ; Xu et al., 2021 ; Bae et al., 2022 ).…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of G. elata has been continuously reported in recent years, offering insights into how G. elata adapted to heterotrophy in Mycena and Armillaria . In G. elata , genes important in the control of flowering time, the circadian clock, nutrient absorption, immunity, growth of the roots and leaves, and photosynthesis were all severely lost ( Yuan et al., 2018 ; Park et al., 2020 ; Xu et al., 2021 ; Bae et al., 2022 ).…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
“…The expansion of many gene families in G. elata is additional evidence for adaptation to the mycoheterotrophic lifestyle of fungi. Phylogenetic analysis showed that the number of genes of G. elata concerned with mycorrhizal association was significantly expanded ( Bae et al., 2022 ; Jiang et al., 2022 ). These phenomena represent evolutionary events and may be the result of G. elata adapting to a heterotrophic lifestyle in the presence of Armillaria ( Yuan et al., 2018 ; Bae et al., 2022 ).…”
Section: Mechanism Of Interaction Between Symbiotic Fungi and ...mentioning
confidence: 99%
“…Gastrodia elata Bl. f. glauca S. chow (GeB) is a non-toxic perennial herbaceous heterotrophic plant with a sweet flavor, smooth texture, and various benefits ( Hong et al., 2018 ; Liu et al., 2018 ; Gong et al., 2021 ; Shan et al., 2021 ; Shan et al., 2021 ; Bae et al., 2022 ). GeB has no roots and no green leaves, so it cannot directly absorb water and inorganic salts from the soil for the growth of its plants, nor it can photosynthesize to produce organic nutrients for itself.…”
Section: Introductionmentioning
confidence: 99%
“…The symbiotic mechanism between G. elata and Armillaria has rarely been revealed from the perspective of Armillaria , and most studies have focused on G. elata . Previous G. elata genomic analyses indicated an expansion of genes for novel metabolic processes and mycorrhizal association [ 9 , 10 ]. Yuan et al [ 9 ] found that strigolactone could stimulate the hyphal branching and development of A. mellea .…”
Section: Introductionmentioning
confidence: 99%